Design Of Sierpinski Gasket Fractal Antenna With Slits For Multiband Application - Mohamad Hafize, Ramli; Mohamad Zoinol Abidin, Abd Aziz; Mohd Azlishah, Othman; Nornikman, Hassan; Muhammad Syafiq, Noor Azizi; Siti Nurfarhanah, Azizul Azlan; Abdul Halim, Dahalan; Hamzah Asyrani, Sulaiman (Penerbit UTM Press, 2016)
There is highly demand of antenna with these characteristics: compact size, low profile and multiband or broadband but at the same time have to maintain antenna parameters. This paper focuses on design of Sierpinski Gasket Fractal Antenna (SGFA) with slits for multiband application. Two methods are applied to this antenna to improve its performance. The first method is by adding two slits on the fractal antenna. The second method is by increasing the number of iterations of the fractal antenna. These methods can improve the return loss and gain of the antenna. The simulation of the designed antenna is carried out by using Computer Simulation Technology (CST) software. The simulated return loss of SGFA with slit is about -20.1 dB and -11.64 dB compare with SGFA without slit -19.25 dB and -12.27 dB at 2.4 GHZ and 5 GHz. While, the gain also increase when slit is added to SGFA. The simulated and measured of antenna parameter is well compared.